Interferon Treatment of Hepatitis C Reinfection after Liver Transplantation: A Meta-Analysis - Yaqin Chen; Gang Wu; Hongmin Zhang; Hua Xu; Hong Li; Ling Chen; Yixuan Yang; Peng Hu; Dazhi Zhang; Hong Ren; Huaidong Hu (Gastroenterology Research and Practice)
Background. Graft reinfection with hepatitis C (HCV) after liver transplantation is a significant problem in transplant hepatology. This meta-analysis was performed to compare the effectiveness and risk of adverse events of interferon-based therapy with no treatment after liver transplantation. Methods. We searched electronic databases up to July 31, 2013, to obtain relevant research reports that satisfied the inclusion criteria. Meta-analyses were done on randomized controlled trials (RCTs) and nonrandomized trials. Results. A meta-analysis was performed on 2 RCTs and 2 cohort studies comprising a total of 326 patients (171 of whom accepted interferon-based antiviral therapy). The treatment group was found to have higher virological response (VR) rates than controls at 12, 24, 48, and 72 weeks. Patients in the antiviral group had higher sustained virological response (SVR) rates and lower mean alanine aminotransferase levels relative to controls at 48 weeks, but more total serious adverse events (AEs) than controls. Conclusions. Interferon-based treatment has some efficacy in the treatment of HCV graft reinfection following liver transplantation.